1995
DOI: 10.3758/bf03210978
|View full text |Cite
|
Sign up to set email alerts
|

An irrelevant speech effect with repeated and continuous background speech

Abstract: The irrelevant speech effect is the impairment of task performance by the presentation of to-be-ignored speech stimuli. Typically, the irrelevant speech comprises a variety of sounds, but previous research (e.g., Jones, Madden, & Miles, 1992) has suggested that the deleterious effect of background speech is virtually eliminated if the speech comprises repetitions of a sound (e.g., "be, be, be") or a single continuous sound (e.g., "beeeeeee"). Four experiments are reported that challenge this finding. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 17 publications
9
59
1
Order By: Relevance
“…1B). Also consistent with previous findings (Jones & Macken, 1993;LeCompte, 1995) the multiple items produced more disruption than the single items did. The literature on irrelevant speech effects between single items and quiet conditions are somewhat mixed.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1B). Also consistent with previous findings (Jones & Macken, 1993;LeCompte, 1995) the multiple items produced more disruption than the single items did. The literature on irrelevant speech effects between single items and quiet conditions are somewhat mixed.…”
Section: Resultssupporting
confidence: 92%
“…The literature on irrelevant speech effects between single items and quiet conditions are somewhat mixed. Effects have been demonstrated with a repeated sound and even with a similar continuous sound compared to quiet in some experiments (Jones et al, 1992a(Jones et al, , 1992bLeCompte, 1995) while in others no reliable effect have been observed (Jones, 1994;Jones & Macken, 1995a,1995b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of the ISE on serial recall have used one list length, typically eight or nine items LeCompte, 1995). However, detrimental effects of irrelevant sounds on recall have been found in adult participants with lists of five to eight letters (Salamé & Baddeley, 1986).…”
Section: The Present Studymentioning
confidence: 99%
“…The phonological loop component is specialized for the storage and rehearsal of verbal material. It has been studied in secondary tasks such as articulatory suppression, word length, phonological similarity, and irrelevant speech (Baddeley, Thomson, & Buchanan, 1975;Colle & Welsh, 1976;LeCompte, 1995;Salame & Baddeley, 1982). In contrast, the visuospatial sketchpad is specialized for the storage and rehearsal of visual and spatial, typically nonverbal, material (see, e,g., Logie, 1995).…”
Section: New Theoretical Approachesmentioning
confidence: 99%